THE INFLUENCE OF PERFORMANCE ASSESSMENT AND EMPLOYEE CAREER DEVELOPMENT TOWARDS EMPLOYEE PERFORMANCE: A STUDY ON INDONESIAN TELECOMMUNICATION INDUSTRY (PT. INTI PERSERO) - Budiawan, Andi (International Journal of Psychosocial Rehabilitation, 2020)
The performance level of employees of PT INTI has not reached the standard of professionalism. Many employees come to the office, fill absences, chat, and go home without work, thus not achieving the goal of good public services. Found there are some employees who commit fraud with absent entrusted to his co-workers by providing email and password and then login to the website of the company that can only be opened with internal WIFI network companies. Besides, the high turnover rate would cause a negative impact on the organization because it creates instability and uncertainty of the labor conditions and increases human resource costs. High turnover lead organization is not effective because companies lose employees who excel and experience to need to retrain new employees. The purpose of this study was to determine how much influence the performance appraisal and career development of employees of the migration levels of employees in PT. Industri Telekomunikasi Indonesia (Persero) either simultaneously or partially. The method used is descriptive and verification. The sampling technique used by the author in this study is simple random sampling technique. Data processing is performed by multiple linear regression analysis, the correlation coefficient, determination coefficient, and hypothesis testing. Based on the research results, variable performance assessment significantly affect the variable the migration levels of employees, variable career developmentsignificantly significantly affects the variable the migration levels of employees, Simultaneous hypothesis test results indicate that there is significant influence of performance appraisal and career development of employees on the migration levels of employees.